Biomimetic Radial Tandem Junction Photodetector with Natural RGB Color Discrimination Capability. Issue 19 (29th August 2017) - Yang, Fan; Wang, Junzhuan; Lu, Jiawen; Yu, Zhongwei; Yu, Linwei; Xu, Jun; Shi, Yi; Chen, Kunji; Roca i Cabarrocas, Pere
Abstract : Imitating natural rod or cone cells in human eyes can inspire a biomimetic design of filter‐free color sensing photodetector with the aid of three‐dimensional (3D) nanophotonic engineering. Here, a novel radial tandem junction (RTJ) super‐rod structure is proposed and demonstrated, which consists of coaxially stacking hydrogenated amorphous silicon PIN junctions upon silicon nanowires, resembling to the live retinal cells in terms of both geometry and dimension. As a consequence, these RTJ units enjoy a unique wavelength‐selective and cavity‐mode‐assisted light absorption/responses in the inner and the outer radial PIN junctions, which are readily tunable to achieve natural RGB color discrimination in the RTJ rod‐cells without the need of any filter system. This unique RTJ design can indicate a new 3D implementation of color sensing photodetectors enabled by advanced nanophotonic structuring and engineering. Abstract : Imitating natural rod or cone cells in human eyes inspires a novel biomimetic design of filter‐free RGB color sensing photodetectors, in a radial tandem junction super‐rod structure that consists of coaxially stacking hydrogenated amorphous silicon PIN junctions upon silicon nanowires, resembling to the live retinal cells in terms of both geometry and dimensions.